Pengaruh Pelatihan dan Pengembangan Terhadap Disiplin Kerja dan Kinerja Karyawan - Sulaefi Sulaefi (University of Merdeka Malang, 2017)
Training and development of human resources is necessary for organization to improve work discipline and performance. The purpose of this study was to analyze the influence of training and human resource development to the work discipline and performance, work discipline on performance as well as to determine the affect of training and development to the performance directly and indirectly through labor discipline. Respondents in this study were 80 employees College of Agricultural Extension (STPP) in Magelang. Methods of data collection using questionnaires and analysis tools used descriptive, regression and path analysis. Results of this study showed, the training and development has an effect on the work discipline and performance as well. Training directly affects to the performance, while the development indirectly effect to the performance through work discipline. https://doi.org/10.26905/jmdk.v5i1.1212